Trimetazidine: Activating AMPK Signal to Ameliorate Coronary Microcirculation Dysfunction after Myocardial Infarction - Xiaolong Qu; Pan Yang; Li Jiao; Yuehui Yin (Frontiers in Bioscience-Landmark)
Background: Myocardial ischemia-reperfusion (I/R) injury and coronary microcirculation dysfunction (CMD) are observed in patients with myocardial infarction after vascular recanalization. The antianginal drug trimetazidine has been demonstrated to exert a protective effect in myocardial ischemia-reperfusion injury. Objectives: This study aimed to investigate the role of trimetazidine in endothelial cell dysfunction caused by myocardial I/R injury and thus improve coronary microcirculation. Methods: The myocardial I/R mouse model was established, and trimetazidine was administered for 7 days before myocardial I/R model establishment. Echocardiography, 2,3,5-triphenyltetrazolium chloride (TTC) staining, hematoxylin-eosin (H&E) staining, and thioflavin S staining were applied to assess myocardial injury and microvascular function. Additionally, the oxygen-glucose deprivation/reperfusion (OGD/R) model was developed in endothelial cells to simulate myocardial I/R injury in vitro. Griess reaction method, immunofluorescence, and western blotting (WB) were employed to detect the expressions of nitric oxide (NO), platelet endothelial cell adhesion molecule-1 (CD31) and vascular endothelial (VE)-cadherin, zonula occludens protein 1 (ZO-1), occludin, vascular endothelial growth factor (VEGF) and adenosine monophosphate (AMP)-activated protein kinase (AMPK) signaling-related proteins in endothelial cells and mouse cardiomyocytes. AMPK pathway inhibitor compound C was used for further mechanism validation. Results: Our research demonstrated that trimetazidine can alleviate myocardial pathological injury and cardiac function injury during myocardial I/R. Trimetazidine was observed to improve microvascular reflux phenomenon and microvascular function and barrier injury in myocardial I/R and OGD/R models. Additionally, the expressions of AMPK signal-related proteins were found to be inhibited in myocardial I/R and OGD/R models, which were then activated in mice administered trimetazidine. However, the effects of trimetazidine on endothelial cell function and barrier damage were attenuated after co-treatment with compound C and trimetazidine. Conclusion: Trimetazidine ameliorated myocardial I/R-induced CMD by activating AMPK signaling.